Effect of Humidity on Partial Discharge Characteristics of Epoxy/Boron Nitride Nanocomposite under High Voltage Stress - Noor ‘Aliaa Awang; Faris Akmal Suhaini; Yanuar Z. Arief; Mohd Hafizi Ahmad; Noor Azlinda Ahmad; Nor Asiah Muhamad; Zuraimy Adzis (Institute of Advanced Engineering and Science, 2017)
Partial discharge (PD) may lead to the degradation of insulating materials and affect the lifetime of high voltage equipment. This paper describes the effect of relative humidity on PD characteristic of epoxy/boron nitride (BN) nanocomposite under high voltage (HV) stress. In this work, CIGRE Method II was utilized as an electrode configuration. BN nanofiller was chosen because of its high insulating properties with high thermal conductivity. The PD characteristics such as PD charge magnitude, PD number or occurrence, and average of PD charge during certain of ageing time under HV stress against relative humidity were examined. The results revealed that PD number of humid samples is higher about 8 14% compared to the normal ones. It is considered due to the decrease of surface resistance of the humid samples. The PD charge magnitudes of humid samples are slightly higher compared to the normal ones. The epoxy/BN nanocomposite has lesser PD number and magnitude compared to the neat epoxy samples.